Homo naledi lumbar vertebrae and a new 3D method to quantify vertebral wedging. Issue 3 (21st September 2022) - Williams, Scott A.; Zeng, Iris; Guerra, Jordan S.; Nalla, Shahed; Elliott, Marina C.; Hawks, John; Berger, Lee R.; Meyer, Marc R.
Abstract: Objectives: In humans and known fossil hominins, lumbar lordosis is produced by vertebral body wedging and other bony and soft tissue features such as the shape of the intervertebral discs. Current techniques for quantifying the wedging of vertebral bodies are limited in utility, especially when analyzing incomplete fossil material. Here, we introduce a 3D method to quantify vertebral body wedging angles that yields the angles between two "best fit" planes in the software GeoMagic Wrap (3D Systems). Materials and Methods: To test that this new method is repeatable with existing methods, we measure the wedging of 320 lumbar vertebrae representing 64 modern human individuals. For each vertebra, wedging angles were calculated from linear measurements taken with calipers and compared with estimates generated from the 3D best fit plane method. We also apply the 3D plane method to fossil hominin lumbar vertebrae, including newly described lumbar vertebrae of Homo naledi, the majority of which do not preserve the four landmarks necessary to calculate wedging angles using the traditional approach. Results: The results of the two methods are highly and significantly correlated ( r 2  = 0.98, p  < 0.0001). The 3D plane method was successfully applied to nearly all of the fossil hominin specimens included in the study. Discussion: The new 3D plane method introduced here is repeatable with the traditional linear measurement method and allows for the estimation of wedging angles in incomplete material. When applied to Homo naledi lumbar vertebrae, similarities to other fossil hominins and modern humans are found.